An energy-efficient wireless sensor network construction algorithm for air quality condition detection system. (May 2021) - De, Sumana; Chakraborty, Baisakhi
Abstract: In India, the Air Quality Index (AQI) is calculated according to the air pollutants' values of PM2.5, PM10, NO2, NH3 SO2, CO, and O3. Firstly, to collect these values from an area, this paper proposes an energy-efficient Wireless Sensor Network layout, constructed by the proposed Almost Equally Dividing Region Clustering algorithm. These values are to be stored at the Internet Website through that network. Secondly, to detect exact air quality conditions, this paper simultaneously proposes the Air Quality Condition Detection System that takes these pollutants' values as the inputs and after the classification calculations displays the air quality condition, AQI range, health impact information for that range. The system classifier model, the Random Forest model provides 93% accuracy, 90% precision, 90% recall, and 89% F1 score. With the same inputs, the system produces the exact result as given in the website 'National Air Quality Index' available at 'https://app.cpcbccr.com/AQI_India/'.